Electronic Band Structure Engineering of Transition Metal Oxide‐N, S‐Doped Carbon Catalysts for Photoassisted Oxygen Reduction and Oxygen Evolution Catalysis. Issue 1 (23rd November 2021) - Xiao, Zuoxu; Lv, Xuehui; Liu, Shanshan; Liu, Qi; Wang, Fuling; Yan, Wei; Xing, Tao; Li, Zhi; Li, Xiyou; Chen, Yanli
Abstract: A novel "dual isolation of metal active sites" heterojunction engineering is developed in this work. The double isolation of the active sites is achieved through MN4 (M = Co, Fe) coordinating bonds in sulfonated‐substituted metalloporphyrin (MTPPS) and electrostatic interactions of MTPPS absorbed with poly(3, 4‐ethylenedioxythiophene) networks. Subsequent "in situ copyrolysis" over the precursors ensures effective contact between p‐type CoFe2 O4 and n‐type Fe2 O3 species with n‐type N, S‐doping carbon support, respectively. This leads to p–n CoFe2 O4 ‐N, S‐C and n–n Fe2 O3 ‐N, S‐C heterojunctions. Meanwhile, CoFe2 O4 ‐N, S‐C has a higher E VB energy level (−6.22 eV) than Fe2 O3 ‐N, S‐C (−6.31 eV), achieving lower energy barrier, and thus superior oxygen reduction reaction (ORR) performance with a higher half‐wave potential (0.84 V) of CoFe2 O4 ‐N, S‐C than Fe2 O3 ‐N, S‐C (0.82 V). In addition, CoFe2 O4 ‐N, S‐C also exhibits higher oxygen evolution reaction (OER) performance with 100 mV lower overpotential (0.41 V) than Fe2 O3 ‐N, S‐C. The lower overpotential is a result of larger energy gap between E CB energy level and Fermi level of CoFe2 O4 ‐N, S‐C. This is the first demonstration of a novel p–n heterojunction with a special band structure that plays a key role in highly active ORR and OER bifunctional catalysis. Moreover, CoFe2 O4 ‐N, S‐C displays significant photoelectrochemical enhancement upon light irradiation. Abstract : The n–n Fe2 O3 ‐N, S‐C and p–n CoFe2 O4 ‐N, S‐C heterojunctions are fabricated through a novel "dual isolation of metal active sites/in situ copyrolysis" strategy for oxygen reduction reaction and evolution reaction catalysis. And detailed study reveal that the special energy band structure of novel p–n heterojunction can ensure efficient charge transport and improve the bifunctional electrocatalytic activity, photosensitivity, and zinc‐air battery performance.